Relationship between anaerobic parameters provided from MAOD and critical power model in specific table tennis test - Zagatto, A. M.; Gobatto, C. A. (International Journal of Sports Medicine, 2012)
The aim of this study was to verify the validity of the curvature constant parameter (W '), calculated from 2-parameter mathematical equations of critical power model, in estimating the anaerobic capacity and anaerobic work capacity from a table tennis-specific test. Specifically, we aimed to i) compare constants estimated from three critical intensity models in a table tennis-specific test (Cf); ii) correlate each estimated W ' with the maximal accumulated oxygen deficit (MAOD); iii) correlate each W ' with the total amount of anaerobic work (W ANAER) performed in each exercise bout performed during the Cf test. Nine national-standard male table tennis players participated in the study. MAOD was 63.0(10.8) mL · kg - 1 and W ' values were 32.8(6.6) balls for the linear-frequency model, 38.3(6.9) balls for linear-total balls model, 48.7(8.9) balls for Nonlinear-2 parameter model. Estimated W ' from the Nonlinear 2-parameter model was significantly different from W? from the other 2 models (P<0.05). Also, none W ' values were significantly correlated with MAOD or W ANAER (r ranged from - 0.58 to 0.51; P>0.13). Thus, W ' estimated from the 2-parameter mathematical equations did not correlate with MAOD or W ANAER in table tennis-specific tests, indicating that W ' may not provide a strong and valid estimation of anaerobic capacity and anaerobic capacity work.